2003
DOI: 10.1002/aic.690491120
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐logic dynamic optimization applied to batch distillation process design

Abstract: An approach for the optimal configuration and sequencing of complex batch-distillation processes is presented. The proposed method is based on formulating a mixed-logic dynamic optimization problem in which a performance index is minimized subject to a disjuncti®e dynamic model and constraints. The disjuncti®e model comprises a gi®en set of equipment modules, such as stacks of trays of different size or feed and product ®essels, a®ailable for the distillation process under consideration along with logical rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…15 Solution methods of MLDOs are discussed along with reformulation techniques for disjunctions and differential algebraic equations (DAEs). To start, we first elucidate how both facets can be tied together in the context of a state equipment network (SEN), which is a flow sheet superstructure we rely on to account for the graphical and also mathematical representation of a process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Solution methods of MLDOs are discussed along with reformulation techniques for disjunctions and differential algebraic equations (DAEs). To start, we first elucidate how both facets can be tied together in the context of a state equipment network (SEN), which is a flow sheet superstructure we rely on to account for the graphical and also mathematical representation of a process.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we show the development of a hybrid discrete-continuous model based on the SEN that eventually gives rise to a mixed-logic dynamic optimization problem (MLDO). 15 Solution methods of MLDOs are discussed along with reformulation techniques for disjunctions and differential algebraic equations (DAEs). Many successful research studies on discrete dynamic systems have been reported from various fields, e.g., integrated design and control, 16 synthesis of rice drying processes 17 and simultaneous scheduling and control optimization in polymer grade transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed-integer optimal control problems (MIOCPs) in ordinary differential equations (ODEs) have gained increasing interest over the last years, see references [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This is probably due to the fact that the underlying processes have a high potential for optimization.…”
Section: Introductionmentioning
confidence: 38%
“…The dynamic models with mixed discrete and continuous variables are called hybrid systems (which are MIDO problems in general). Start-up and shut-down operations [262], batch systems [263], and grade transitions [258,259] are some of the main applications of optimization of hybrid systems. Several hybrid formulations have been developed and implemented in recent years [264][265][266][267][268][269][270][271].…”
Section: Process Controlmentioning
confidence: 45%